The impact of regulation, ownership and business culture on managing corporate risk within the water industry - Allan, Richard; Jeffrey, Paul; Clarke, Martin; Pollard, Simon J. T. (IWA Publishing, 2013)
Although the specifics of water utility ownership, regulation and management culture have been explored in terms of their impact on economic and customer value, there has been little meaningful engagement with their influence on the risk environment and risk management. Using a literature review as the primary source of information, this paper maps the existing knowledge base onto two critical questions: what are the particular features of regulation, ownership and management culture which influence the risk dynamic, and what are the implications of these relationships in the context of ambitions for resilient organizations? In addressing these queries, the paper considers the mindful choices and adjustments a utility must make to its risk management strategy to manage strategic tensions between efficiency, risk and resilience. The conclusions note a gap in understanding of the drivers required for a paradigm shift within the water sector from a re-active to a pro-active risk management culture. A proposed model of the tensions between reactive risk management and pro-active, adaptive risk management provides a compelling case for measured risk management approaches which are informed by an appreciation of regulation, ownership and business culture. Such approaches will support water authorities in meeting corporate aspirations to become "high reliability" services while retaining the capacity to out-perform financial and service level targets.